Validation of OpenFOAM® for Oscillating Water Column three-dimensional modeling. (1st October 2015) - Iturrioz, A.; Guanche, R.; Lara, J.L.; Vidal, C.; Losada, I.J.
Abstract: A new solver for wave and structure interaction is used for three-dimensional simulation of an Oscillating Water Column (OWC). The CFD model solves the Reynolds Averaged Navier–Stokes equations for two incompressible phases (water and air). Laboratory experiments are conducted on a small scale to validate the numerical results. Air and water pressures and velocities as well as the free surface evolution inside and outside the chamber are modeled with notably good agreement. The model is further used to improve understanding of relevant processes and shows potential for use detailed analysis. Even if the experimental problem analyzed had a two-dimensional behavior, the three dimensional domain of the wave flume was numerically simulated in order to prove the capabilities of OpenFOAM ® . Abstract : Highlights: OWC "behaviour" is simulated using OpenFOAM for detailed dynamics analysis and understanding. Results are validated with experimental data. Free surface, air pressure and air flow data are validated.